(untitled) (Ágora Journal, 2025)
The purpose of this article is to examine the social contradictions present in provincial administration during the end of the Roman Republic. Initially, we will seek to present the organizational form of the provinces: how management logistics were carried out, which positions were assigned below the governors, how provincial management positions were distributed and what reforms these underwent and why they occurred. Consequently, we will comment on the provincial commands of Appius Claudius Pulcher (53 - 51 BCE) and Cicero (51 - 50 BCE), as presented in their epistles, in order to address how indebtedness acted in the relationship of domination built between the elites in the center of the empire and its provincial peoples.